Proposed Nodal Cancer Index (NCI) in ovarian carcinomatosis - M D Ray; Manish Kumar Gaur (Journal of the Egyptian National Cancer Institute)
Abstract Introduction The nodal positivity in advanced ovarian cancers is approximately 68–70% histopathologically. Even after neoadjuvant chemotherapy (NACT) chance of nodal positivity is around 50–80%. In the prevailing literature, the nodal burden is a neglected entity in both assessment and documentation and complete clearance during the CRS. We aim to highlight the importance of nodal dissection and propose a Nodal Cancer Index (NCI) like PCI for ovarian cancers based on our experience of 105 cases. Materials and methods We included 105 patients with advanced ovarian cancers who underwent CRS. Retroperitoneal lymph nodes and bilateral pelvic lymph node dissection were routinely done in all the cases. For Nodal Cancer Index calculation, the abdomen is divided into 13 zones, zones 1–6 for retroperitoneum, zones 1–6 for Pelvic nodes, and zone 0 for extra-abdominal nodes. Furthermore, a Nodal size score ranging from 1 to 3 has been proposed so that the Nodal Cancer Index ranges from 13 to 39. Results The median age of the patients was 51 years (range 19–71) and the most significant patients were in stage III (65.7%), and 34.3% had stage IV disease at presentation. The lymph nodes were found to be positive in 62 patients (59%), and the positivity rate was higher in patients who underwent upfront surgery 36 (58.1%) as compared to 26 (41.9%) in those who received NACT. The majority of the patients (56.6%) had positive lymph nodes in both the pelvic and retroperitoneal groups, whereas 19.3% had only pelvic nodes positive, and 24.2% had only retroperitoneal nodes positive. The probability of overall survival at 5 years in our patients was 48.9% (95% CI = 35.5–61). Conclusion The results of our analytic observation confirm that systemic lymphadenectomy of all 13 zones proposed by our study should be an integral part of optimal CRS in the advanced carcinoma ovary and this will help us manage these advanced cases in a better objective manner.